Science Mapping the Academic Knowledge on Business Improvement Districts - Silva, Diogo Gaspar (2022)
Business Improvement Districts (BIDs) are a contemporary urban revitalization policy that has been set in motion through international policymaking circuits. They have been presented as a panacea to the economic and social challenges facing many cities and traditional shopping districts. However, a comprehensive overview of the academic literature on this form of local governance remains to be conducted. Drawing on bibliometric methods and bibliometrix R-tool, this paper maps and examines the state-of-the-art of academic knowledge on BIDs published between 1979 and 2021. Findings suggest that (i) scientific production has increased since the early 2000s, has crossed US borders but remains highly Anglo-Saxon-centered; (ii) academic knowledge on BIDs is multidisciplinary and has been published in high-impact journals; (iii) influential documents on BIDs have centered on three issues: urban governance/politics, policy mobilities–mutation and impacts assessment and criticisms; (iv) while author collaboration networks exist, the interaction between them is limited; (v) the conceptualization of BIDs has changed over time, both in thematic and geographical focus. These results constitute the first science mapping on the academic literature on BIDs, and we argue they should inform future scientific debates about the studying of this form of local governance.